Development and characterization of iron (III) phthalocyanine modified carbon nanotube paste electrodes and application for determination of fluometuron herbicide as an electrochemical sensor - Demir, Ersin; Goktug, Ozge; Inam, Recai; Doyduk, Dogukan (ELSEVIER SCIENCE SA, 2021)
This study is the first electroanalytical study conducted for the determination of fluometuron herbicide. For this purpose, a new electrode was prepared by combining iron (III) phthalocyanine - 4.4',4'',4'''-tetrasulfonic acid, oxygen monosodium salt hydrated compound (FePc) and multi-walled carbon nanotube powders (MWCNTP). The FePc/MWCNTP composite (hybrid) material prepared in this way was coated on glassy carbon electrode (GCE) and multi-walled carbon nanotube paste electrode (MWCNTPE) using the drop-dry method. Compared to both the bare GCE and MWCNTPE, the modified FePc/MWCNTPE increased the anodic peak current of fluometuron by approximately six fold. Calibration plots of the fluometuron were constructed using the standard addition method with differential puls stripping voltammetry (DPSV) and square wave stripping voltammetry (SWSV) under the optimum conditions. While the working range was determined as 0.4-15.0 mg/L in pH 6.0 Britton Robinson (BR) buffer solution on FePc/MWCNTP electrode with DPSV, this range was found to be 0.4-7.5 mg/L with SWSV. In addition, the limit of detection (LOD) and the limit of quantification (LOQ) values were 69.8 mu g/L and 233.0 mu g/L, respectively, by DPSV. On the other hand, these two validation values (LOD and LOQ) were 101 mu g/L and 337 mu g/L by SWSV, respectively. Subsequently, cyclic voltammetric (CV) studies were carried out to elucidate the electrochemical behavior and electrode mechanism of the fluometuron herbicide. In addition, the interference effects of some cations and pesticides in the determination of fluometuron were examined. Finally, studies of recovery of fluometuron herbicide from tap water and determination of fluometuron in Cottonex 500 SC (R) commercial pesticide formulation using the proposed DPSV method and modified FePc/MWCNTP electrode were performed with very low relative error.
Keywords: Fluometuron; Modified Electrode; Phthalocyanine; Electrochemistry; Determination; POTENTIAL SWEEP VOLTAMMETRY; PHENYLUREA HERBICIDES; LIQUID-CHROMATOGRAPHY; GAS-CHROMATOGRAPHY; DIODE-ARRAY; WATER; MICROEXTRACTION; FLUORESCENCE; HPLC; Chemistry